Macroeconomic Effects of Market Structure Distortions : Evidence from French Cartels - Moreau, Flavien; Panon, Ludovic.. (Washington, D.C. : International Monetary Fund, 2022)
We provide systematic evidence on cartels' characteristics, using novel data on cases investigated by the French Competition Authority. These practices are widely spread across sectors and cartel members are typically among the top firms in their industries. In a model with heterogeneous firms and collusion, cartels amplify misallocation by charging supracompetitive markups. Breaking down French cartels would increase aggregate productivity by 2%, welfare by 3.5%, bringing the economy 37% closer to the efficient frontier. These numbers shed light on the aggregate importance of collusion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Antitrust Law; Horizontal Anticompetitive Practices; Market Structure and Pricing; Monopolization; Oligopoly and Other Imperfect Markets